Structure Design and Magnetic Field Simulation of Non-contact Nutation Reduction Motor - Xiaqi Shan; Ligang Yao; Meiyan Lou; Yicheng Chen (Jixie chuandong)
In order to solve the problem of weak stiffness of flexible wheels and more mechanical friction in existing robot harmonic reducer motors, a new type of nutation reducer motor is proposed by combining nutation deceleration motion with magnetic meshing principle. The structural characteristics and transmission mode are described, and the design method and parameter selection are given. The internal magnetic field characteristic and the torque angle characteristic of the reduction motor are analyzed by using Maxwell finite element software.